2016
DOI: 10.3928/1081597x-20151229-03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Femtosecond Laser-Assisted Cataract Pretreatment on Pupil Diameter: A Comparison Between Three Laser Platforms

Abstract: FLACS pretreatment seems to induce significant pupillary miosis with all laser platforms assessed in this study. The decrease in pupil diameter after FLACS reached clinical significance for cataract extraction (< 5 mm) in 4.0% of cases, whereas 20.2% of eyes demonstrated small pupil diameter (≤ 6 mm) after FLACS pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 14 publications
0
30
2
Order By: Relevance
“…A recent comparative series investigating pupil diameter before and after laser cataract surgery reported that laser pretreatment induced significant pupillary miosis with the pupil diameter falling below 5 mm in 4.0% of cases. 25 In a series of 1500 laser cataract operations, the intraoperative pupil constriction rate was reduced from 9.5% in the first 200 cases to 1.2% for the latter 1300 cases when an additional one drop of 10% phenylephrine was given after the laser procedure. 12 The authors also noted that factors such as platform evolution, which shortened overall procedure time, and more efficient scanning patterns that reduced the required delivered energy, may also have been partly attributable.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative series investigating pupil diameter before and after laser cataract surgery reported that laser pretreatment induced significant pupillary miosis with the pupil diameter falling below 5 mm in 4.0% of cases. 25 In a series of 1500 laser cataract operations, the intraoperative pupil constriction rate was reduced from 9.5% in the first 200 cases to 1.2% for the latter 1300 cases when an additional one drop of 10% phenylephrine was given after the laser procedure. 12 The authors also noted that factors such as platform evolution, which shortened overall procedure time, and more efficient scanning patterns that reduced the required delivered energy, may also have been partly attributable.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Researchers believe that increased levels of prostaglandin E2 (PGE2), as measured immediately after laser pretreatment, are responsible for intraoperative narrowing of the pupil. [12,13,14,15] PGE2 is released when ocular tissue is exposed to femtosecond laser cutting side effects. [16]…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not test other modules on the Z8, it can also be used for refractive surgery and keratoplasty which could be beneficial when sharing the device among other departments in a comprehensive ophthalmic teaching center. Moreover, studies have shown pupil miosis after femtosecond laser application during FLACS [ 24 , 25 ]. However, in our study, we did not use any preoperative non-steroidal anti-inflammatory eye drops and still did not find significant pupil miosis.…”
Section: Discussionmentioning
confidence: 99%